Agomelatine, a novel intriguing antidepressant option enhancing neuroplasticity: A critical review. (August 2013) - Pompili, Maurizio; Serafini, Gianluca; Innamorati, Marco; Venturini, Paola; Fusar-Poli, Paolo; Sher, Leo; Amore, Mario; Girardi, Paolo
Abstract Objectives. The treatment of major affective disorders, commonly associated with high disability and elevated social costs may be still considered unsatisfactory. Among all antidepressant drugs, predominantly acting through monoaminergic mechanisms, agomelatine is of particular interest due to another alternative mechanism of action. Targeting melatonergic receptors, agomelatine play a crucial role in synchronizing circadian rhythms, known to be altered in depressed subjects. Methods. A critical review of the literature focusing on efficacy, safety and tolerability of agomelatine in major affective disorders was performed. Additionally, we focused on the potential of agomelatine in enhancing neuroplasticity mechanisms and promote neurogenesis. A total of 136 articles from peer-reviewed journals were identified, of which 50 were assessed for eligibility and 21 were included. Results. Agomelatine, a melatonergic analogue drug acting as MT1/MT2 agonist and 5-HT2C antagonist, has been reported to be effective as antidepressant drug. Studies confirmed not only clinical efficacy but also safety and tolerability of agomelatine. Also, it enhances neuroplasticity mechanisms and adult neurogenesis in brain areas such as hippocampus and prefrontal cortex. Conclusions. Agomelatine actually represents an intriguing option in the treatment of affective disorders.